AUSTRALIAN FOREIGN POLICY TOWARDS INDONESIA RELATED EAST TIMOR 1975-1991 - Qunuri, Ririn; Pradjoko, Didik, Dr. (UI Scholars Hub, 2021)
This article will explain Australia's attitudes and views on the East Timor issue which caused conflict with Indonesia. But on the other hand, Australia cannot ignore Indonesia's interests in East Timor. In 1978, Australia recognized East Timor